Binder‐Free Electrodes of CoAl Layered Double Hydroxide on Carbon Fibers for All‐Solid‐State Flexible Yarn Supercapacitors. Issue 8 (21st April 2016) - Jagadale, Ajay D.; Guan, Guoqing; Li, Xiumin; Du, Xiao; Ma, Xuli; Hao, Xiaogang; Abudula, Abuliti
Abstract: Yarn supercapacitors have received much attention because of their noticeable role in advanced technologies, such as microrobots, wearable electronic textiles, and implantable medical devices. They can be prepared with different carbon‐based materials, but many devices suffer from low energy densities. Conformally loaded, Faradaically active CoAl‐based layered double hydroxides (CoAl LDH) are loaded onto carbon fiber (CF) yarns to prepare supercapacitors with enhanced capacitance and energy density, avoiding the need for binding agents. The effect of different CoAl LDH loading amounts on morphological, structural, and electrochemical properties is studied, and a loading amount of 2.3 mg cm −2 is found to achieve the maximum specific capacitance of 634.3 F g −1 at a current density of 1 Ag −1 . Flexible all‐solid‐state supercapacitor based on CoAl LDH@CF yarns offers excellent areal capacitance (195 mF cm −2 ) and volumetric energy density (1.6 mWh cm −3 ) with 94 % cyclic stability after 4000 galvanostatic charge–discharge (GCD) cycles. The energy density and flexibility of this CoAl LDH@CFs yarn‐based all‐solid‐state supercapacitor offer great potential for energy management in flexible electronics. Abstract : Flexitime : A uniform and axial loading of CoAl LDH nanosheets on the surface of carbon fiber (CF) yarns is achieved by a facile electrodeposition method, yielding all‐solid‐state flexible yarn supercapacitors that do not require binding agents. The yarn supercapacitors exhibit high energy densities and excellent flexibilities, giving them much potential for application in flexible energy storage systems.